2011
DOI: 10.1002/pd.2854
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of corpus spongiosum in male fetuses

Abstract: We established measurements of the length of fetal corpus spongiosum and a correlation between the former and the penile length. These references can be useful when fetal genital anomalies are suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Although we cannot make a physical examination like pediatricians, obstetric ultrasound allows the detailed evaluation of the male genitalia, including the size of the penis, the size of the scrotum, and the size and location of the testicles [ 22 ]. It is possible to measure variables of the penis such as its length, width, and diameter, as well as that of the comprising structures such as the corpus cavernosum, corpus spongiosum, and glans [ 23 ].…”
Section: Measurement Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…Although we cannot make a physical examination like pediatricians, obstetric ultrasound allows the detailed evaluation of the male genitalia, including the size of the penis, the size of the scrotum, and the size and location of the testicles [ 22 ]. It is possible to measure variables of the penis such as its length, width, and diameter, as well as that of the comprising structures such as the corpus cavernosum, corpus spongiosum, and glans [ 23 ].…”
Section: Measurement Techniquementioning
confidence: 99%
“…Other authors have reported measurement strategies using alternative features. The length of the fetal penis has been measured from the tip of the glans to the pubic symphysis [ 12 ], to the proximal edge of the corpus cavernosum [ 29 ], and to the proximal edge of the corpus spongiosum [ 23 ]. Although correlation between OPL and these measures of “total penile length” was high and authors provided instructions for simplifying these measurements, no later work has repeated these methods.…”
Section: Measurement Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Later in pregnancy, assignment is based on direct visualisation of the genital anatomy, including the scrotum and midline raphe of the penis in males, and the three lines, representing the labial lines, and uterus in female fetuses. There are charts of fetal penile length available but their utility has yet to be proven and different publications give slightly different normal ranges [5,6]. Three-dimensional ultrasound is of limited use for sonographic sex determination in routine practice, but it may be useful in defining malformations of the external genitalia.…”
Section: Normal Appearances and Evaluation Of Fetal Genitaliamentioning
confidence: 99%